Evaluation of Efficacy and Safety of Combined Therapy of Melasma by using Azelic, Glycolic and Kojic Acid (Unitone and Neotone) - Ahmed Hasan, Intisar; Kh Ibrahim Al-Kayally , Khudhair (Diyala Journal of Medicine, 2023)
Background: Melasma is one of the most common disorders of brown hyperpigmentation, which affect primarily the face and later on some other sites of the body , seen most commonly in women during the reproductive period and may seen in men . Many options are used in the treatment of melasma, most commonly: hydroquinone, tretenoin, corticosteroid, azelic acid, glycolic acid, kojic acid, triaximinic acid, ascorbic acid, intralesional glutathione, and lastly medical procedures, like: microdermabrasion, chemical peel, laser and light therapy. Objective: To evaluate the efficacy and safety of combined therapy (azelic, glycolic and kojic acids) in the treatment of melasma (UNITONE and NEOTONE) . Patients and Methods: A cross-sectional study in which (585) patients complaining of melasma (577 females and 8 males), their age ranged from (17-50) years, with a mean age of 46.15± years. Treated by application of azelic acid (20% cream) for two hours at night, then washed and followed by topical application of combined cream consisted of (5%) glycolic acid and (1%) kojic acid throughout the night and washed in the morning, with application of sun block of ≥50 SPF, and oral ascorbic acid (500mg) tablet twice in the morning and evening . Results: Out of 585, 98% was females with a mean age of (46.15±8) years. Eight percent of the patients of MAIS score-1, (22.05%) of score-2, (51.28%) of score-3 and (18.8%) of score-4. Regarding the response to therapy: (44.78%) of patients showed complete clearance of the disease, (48.85%) with good response, (1.7%) of poor response and (5.47%) showed relapse of the melasma after discontinuation of the therapy, and they were retreated by the same combined formula, (93.75%) of them cleared completely and (6.25%) showed good response. Ninety percent of patients developed a variable degree of irritation, erythema and burning sensation, at the beginning of the treatment and after (10-15) days, most of them tolerated the therapy. Conclusion: Combined therapy of azelic, glycolic and kojic acids was effective and safe in the treatment of melasma and this combination was superior and alternative to the ordinary and corner therapy of hydroquinone and corticosteroid.